Impact of COVID-19 confinement on quality of life and mental health - Ballena, Catherin L. (2021)
Introduction: The SARS-Cov-2 pandemic has had a negative impact on multiple aspects of human life, both physical, psychological, economic, social and cultural. Quality of life conditions are associated with confinement and freedom to go out, to spend time with friends or family, or to carry out activities; so they are deprived of most of their social interaction. The objective of this present article is to provide information on how confinement and social isolation due to the pandemic affects quality of life and mental health